Housing policy in deregulated urban land markets - Francisco Vértiz; Violeta Ventura (Oñati Socio-Legal Series)
In the paper is analyzed the implementation of the Programa Crédito Argentino del Bicentenario (PRO.CRE.AR) in the city of La Plata. Specifically, it is studied how did the state deal with the urban land demands of PRO.CRE.AR’s beneficiaries, and their role in the policy making process. From a socio-legal perspective is reconstructed/analyzed the social process prior to the state’s legal response, recovering the political scope of the legal phenomenon. It also considered how the actor’s strategies were restructured facing into account their legal expectative and its influence in the urban legislation. It is concluded that the ways of resolving the land problem by local government, validated by the provincial state, were based mainly on the relaxation of urban legislation and enabled peripheral urbanization processes, with low quality urban environmental and appropriation of urban surplus values.